Pengaruh ESG Disclosure terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi: Studi Kasus Perusahaan yang Terdaftar di BEI Tahun 2020-2023 - Amalia Sabila Khairina Akri; Irene Rini Demi Pangestuti (Diponegoro Journal of Management, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) Disclosure on firm value, as measured by Tobin’s Q, and to examine the moderating role of firm size. The research utilizes secondary data from companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The analytical methods employed are multiple linear regression and Moderated Regression Analysis (MRA). The results reveal that Social Disclosure, Environmental and Governance dimensions do not show significant effects. Moreover, firm size does not significantly moderate the relationship between ESG dimensions and firm size. These findings indicate that the effectiveness of ESG disclosure in enhancing firm value depends on the type of ESG information disclosed and company characteristics. This study provides insights for companies and stakeholders to improve ESG practices in a more strategic and impactful way.